2003
DOI: 10.1086/376557
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Novel Vaccinia‐Neutralization Assay Based on Reporter‐Gene Expression

Abstract: In anticipation of large-scale smallpox vaccination, clinical trials of new vaccine candidates with improved safety profiles, and new vaccinia immune globulin (VIG) products, there is an immediate need to develop new assays to measure vaccinia-specific immune responses. The classical assay to measure vaccinia neutralization, the plaque-reduction neutralization test (PRNT), is slow, labor intensive, and difficult to validate and transfer. Here we describe the development of a novel vaccinia-neutralization assay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 18 publications
2
44
0
Order By: Relevance
“…Inasmuch as smallpox vaccination was discontinued more than 30 years ago, one possible use for this epitope would be to detect a long-term memory response, or the response to the epitope could be used as a criterion of effective immunization. This could be utilized in addition to other methods for detection of effective poxvirus immunity or vaccine "take," such as the recently developed vaccinia virus neutralization assay (35), or it could be used to look for long-term immunity to poxviruses in human subjects (25).…”
Section: Discussionmentioning
confidence: 99%
“…Inasmuch as smallpox vaccination was discontinued more than 30 years ago, one possible use for this epitope would be to detect a long-term memory response, or the response to the epitope could be used as a criterion of effective immunization. This could be utilized in addition to other methods for detection of effective poxvirus immunity or vaccine "take," such as the recently developed vaccinia virus neutralization assay (35), or it could be used to look for long-term immunity to poxviruses in human subjects (25).…”
Section: Discussionmentioning
confidence: 99%
“…NAb responses against vaccinia virus were measured using a luciferase-based assay in HeLa cells essentially as previously described for a ␤-galactosidase neutralization assay (20). We measured the reduction in luciferase reporter gene expression in target cells after a single round of virus infection.…”
Section: Methodsmentioning
confidence: 99%
“…Subtyping studies demonstrated that these antibodies were predominantly IgG2a and IgG1 (data not shown). We next assessed vaccinia virus IMV-specific NAb titers by using a luciferase-based virus neutralization assay (20). As shown in Fig.…”
Section: Humoral and Cellular Immune Responses Elicited By Rad35 Vectmentioning
confidence: 99%
“…We adapted a vaccinia-specific neutralization assay originally developed at the Food and Drug Administration (FDA) to measure neutralizing antibody titer (15,19). Briefly, heat-inactivated serum samples were serially diluted and then mixed with a known quantity of a recombinant b-galactosidase (b-gal) expressing VACV for 1 h. Serum samples were then incubated with HeLa cells overnight.…”
Section: Vaccinia-neutralizing Antibody Assaymentioning
confidence: 99%